Peningkatan hasil belajar melalui penggunaan e-modul tata rias geriatri berbasis pendekatan saintifik pada siswa Kelas XI Tata Kecantikan SMKN 27 Jakarta - Natasya, Amelia; Supiani, Titin; Hidayah, Nurul (Academy of Education Journal, 2024)
Many of the final research (thesis) students from the UNJ Cosmetology Education study program have produced various kinds of learning media, one of which is in the form of e-modules, but most of the learning media have not yet reached the implementation stage. At SMKN 27 Jakarta there are problems with student learning outcomes which are still lacking theoretically in the geriatric cosmetology sub-material and have never used learning media in the form of e-modules in the learning process. This research aims to determine student learning outcomes before using the geriatric facial make-up e-module in class The research method used in this research is classroom action research (PTK) with the Kemmis & McTaggart model which consists of 4 stages, namely planning, implementing actions, observing and reflecting. The results of this research starting from cycle I which carried out a pre-test obtained an average student score of 75,27 with a classical learning completeness percentage of 58,33% (21 students). After the end of cycle I the students' average score increased to 88,33 with a classical learning completeness percentage of 75% (27 students). Because cycle I had not yet reached the criteria for research success, cycle II was continued which obtained an average student score of 93,44 with a classical learning completion percentage of 97,22% (35 students). Thus it can be said that the use of e-modules of geriatric cosmetics based on scientific approach in class XI in SMKN 27 Jakarta can improve student learning results because they have achieved the criteria of research success, i.e. increased learning intensity of classical students by 90%.